PENGARUH METODE THE SIX THINKING HATS TERHADAP KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN PKn KELAS XI SMA NEGERI 4 KAYUAGUNG KABUPATEN OGAN KOMERING ILIR SUMATERA SELATAN - citra lidiawati (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2021)
The problem in this study is is there any effect of the six thinking hats method on student learning activeness in Civics Class XI subjects at Kayuagung State High School 4 Ogan Komering Ilir Sumatera Selatan. District. The purpose is to find out whether there is an influence of the six thinking hats method on the activity of students in PPKn subjects. The method used was a quasi-experiment. As a test data collection technique used is the observation sheet. The data analysis technique used is the calculation of the t-test using SPSS 22. The results of this study indicate that there are differences in the results of the activity test between the experimental class and the control class. The average value of the initial test of the activity of the experimental class students 51.25 and the final test 84.00. The average value of the initial control class 51.41 and the final test 70.84. The results of data analysis showed that the average learning outcomes of the experimental class were greater than the control class, namely 70.53> 57.61. Based on the results of the first analysis shows that tcount (7,566) is higher than ttable (1,669) with a degree of validity 62 (df 62) at the level of significance of probability below 0.05 or 0,000 <0.05. This means that H0 is rejected, and Ha is accepted. In other words, the six thinking hats method has a positive influence on student learning activeness in PPKn subjects.